2017
DOI: 10.1038/s41598-017-10000-1
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid resistive pulse-optical detection platform for microfluidic experiments

Abstract: Resistive-pulse sensing is a label-free method for characterizing individual particles as they pass through ion-conducting channels or pores. During a resistive pulse experiment, the ionic current through a conducting channel is monitored as particles suspended in the solution translocate through the channel. The amplitude of the current decrease during a translocation, or ‘pulse’, depends not only on the ratio of the particle and channel sizes, but also on the particle position, which is difficult to resolve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 41 publications
(58 reference statements)
2
22
1
Order By: Relevance
“…As expected, when comparing the pulse duration for two gates differing in length (at same flow rate and same electrical detection principle), it was found that longer gate provides longer pulses ( Figure 3A, B) [13]. Interesting findings have been published by Hinkle et al describing particle trajectories in a hybrid resistive pulse -optical microfluidic platform [13]. This paper describes how the particle position relates to a pulse generation and its intensity, moreover they also tested different sensing gate geometries, where a wider cavity in the middle of the gate produced double peak pulses ( Figure 3C).…”
Section: Mode Sensingsupporting
confidence: 78%
See 2 more Smart Citations
“…As expected, when comparing the pulse duration for two gates differing in length (at same flow rate and same electrical detection principle), it was found that longer gate provides longer pulses ( Figure 3A, B) [13]. Interesting findings have been published by Hinkle et al describing particle trajectories in a hybrid resistive pulse -optical microfluidic platform [13]. This paper describes how the particle position relates to a pulse generation and its intensity, moreover they also tested different sensing gate geometries, where a wider cavity in the middle of the gate produced double peak pulses ( Figure 3C).…”
Section: Mode Sensingsupporting
confidence: 78%
“…The simplest shape used as a sensing gate is depicted in Figure A which is a narrowed channel representing physical constriction. As expected, when comparing the pulse duration for two gates differing in length (at same flow rate and same electrical detection principle), it was found that longer gate provides longer pulses (Figure A, B) . Interesting findings have been published by Hinkle et al .…”
Section: Principle and Design Approachessupporting
confidence: 69%
See 1 more Smart Citation
“…When integrated into microfluidic systems, this 1950's technology is finding new applications. [5][6][7][8][9] New manufacturing processes, coupled with improved electronics have enabled them to characterise analytes' sizes [10][11][12] , concentrations 13,14 , shapes 15 and charges. 16,17 As a result, RPS has found numerous applications within environmental monitoring of, for example: bacteria 18 , algae 19 , and heavy metal ions 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state nanopores and nanochannels offer an attractive alternative that is characterized by high design versatility and operative soundness. Among the advantages of solid-state nanopores, one should mention the combination of well-defined geometry and size, the mechanical, thermal and chemical stability, and, usually, high suitability to optical and electrical experimental techniques [17][18][19]. Usually, solid-state nanochannels are produced on Si, SiO 2 or glass substrates by using high-resolution nanopatterning techniques such as focused ion beam (FIB) milling, e-beam lithography (EBL) or laser machining [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%